2015
DOI: 10.1007/s00204-015-1636-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and elimination of methyl, iso- and n-butyl paraben in human urine after single oral dosage

Abstract: Parabens are used as preservatives in personal care and consumer products, food and pharmaceuticals. Their use is controversial because of possible endocrine disrupting properties. In this study, we investigated metabolism and urinary excretion of methyl paraben (MeP), iso-butyl paraben (iso-BuP) and n-butyl paraben (n-BuP) after oral dosage of deuterium-labeled analogs (10 mg). Each volunteer received one dosage per investigated paraben separately and at least 2 weeks apart. Consecutive urine samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(56 citation statements)
references
References 48 publications
1
45
1
4
Order By: Relevance
“…Benzoic acid is recognized as a nonspecific marker of parabens (Ye et al, 2006). In the present study, p-hydroxybenzoic acid, the reported common metabolite of all paraben esters Wang et al, 2015;Moos et al, 2015;Wang and Kannan, 2016), was not detected in the samples upon GC-MS analysis, while we did not detect the metabolite in the MP and PP controls as well. Therefore, it is possible that p-hydroxybenzoic acid was further oxidized to benzoic acid by mixed microbes during the rapid aerobic degradation process.…”
Section: Possible Biodegradation Products Of Mp and Ppcontrasting
confidence: 70%
“…Benzoic acid is recognized as a nonspecific marker of parabens (Ye et al, 2006). In the present study, p-hydroxybenzoic acid, the reported common metabolite of all paraben esters Wang et al, 2015;Moos et al, 2015;Wang and Kannan, 2016), was not detected in the samples upon GC-MS analysis, while we did not detect the metabolite in the MP and PP controls as well. Therefore, it is possible that p-hydroxybenzoic acid was further oxidized to benzoic acid by mixed microbes during the rapid aerobic degradation process.…”
Section: Possible Biodegradation Products Of Mp and Ppcontrasting
confidence: 70%
“…This is due, in part, to their low metabolic stability and fast excretion with 81–85% excreted in the urine after the first 24 h and over half of that excreted as p -hydroxyhippuric acid, the primary metabolite (Moos et al, 2015). Despite the rapid metabolism, the high prevalence of these products may result in regular daily exposure, as evidenced by a high incidence of detection in urine (Ye et al, 2006; Tefre de Renzy-Martin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Parabens are commonly detected in urine as the parent compound (largely conjugated). Newly identified specific oxidative metabolites may be more specific indicators of exposure than the parent compounds [9]. Triclosan and triclocarban have been banned recently for soaps, but still exist as biocides in many products [10].…”
Section: Resultsmentioning
confidence: 99%